Capacidade resistente de vigas mistas parcialmente revestidas formadas por perfil celular e laje alveolar em piso de pequena altura - Pereira Júnior, Sineval Esteves (2022)
The slim floor systems are characterized by partially encased beam, usually asymmetrical steel profile, configuring a partially encased composite beam. This research aims to evaluate the structural behavior of partially encased composite beams with concrete hollow core slabs and steel cellular profile, under flexural condition. The main aspects evaluated were the flexural strength and failure modes. Numerical modeling of 46 partially encased composite beams under bending tests was developed in ABAQUS® software. Numerical models and procedures were validated from experimental tests of partially encased composite beams in slim floor systems published by several researchers. The main parameters evaluated were the diameter of the reinforcing bars, steel web and flange thicknesses, diameter and number of web openings in cellular profile, concrete topping thickness and the width of the slab. The numerical study revealed the contribution of reinforcing bar in the resistance of the steel-concrete shear connection and consequent increase of the bending resistance. The increase of the steel web and flanges thickness resulted in a significant increase in the strength capacity of the composite beam and reduced values of web thickness compromise the section capacity. The increase in the width of the slab and concrete topping thickness, the composite section presented increased strength and stiffness. Increasing the diameter of the web openings significantly reduced the stiffness and strength of the composite beam. In addition to the numerical program, an initial analytical model was developed to determine the bending moment. The results of the numerical analysis were compared with the equation proposed to determine the bending moment. The analytical model demonstrated coherence and satisfactory correlation with numerical results, and efficiency of the infill concrete in circular openings in the encased steel beam as a shear connector.